Experimental evaluation of the sound absorption and insulation of an innovative coating through different testing methods. Issue 3 (September 2017) - Scamoni, Fabio; Piana, Edoardo A; Scrosati, Chiara
The Lombardy Region and the Construction Technologies Institute of the National Research Council of Italy are promoting the development of an innovative coating nano-material for building retrofitting. The research aims at obtaining a material with higher sound absorption features when compared to conventional plasters, as well as fair thermal and sound insulation performances. In both design and testing stages, it is important to identify and measure key acoustic parameters. This article presents the characterisation of the new material in terms of sound absorption and insulation by means of reverberation room, impedance tube, sound transmission rooms and mobility measurements, together with a discussion on the limits and reliability of the different methods in relation to the specific frequency range and the peculiarities of the material under test. This study contributes to the definition of test procedures that can be applied to other noise-reducing treatments including meta-materials.